Relativistic oscillators in the context of MS noncommutative model. (29th July 2020) - Hamil, B.; Merad, A.; Merad, M.
Abstract: In this letter, the relativistic oscillators in dimensions in the context of the Magueijo-Smolin (MS) noncommutative model are considered. In order to appreciate the influence of this deformation, the energy eigenvalues and eigenfunctions are determined for both cases for the Klein-Gordon and the Dirac oscillators. Our calculations show however that the energies and wave functions of the relativistic oscillator are modified by the deformation parameter.